ULAM-HYERS STABILITY OF A FIXED POINT EQUATION VIA GENERALIZED PICARD OPERATORS - Nanan, N. (Journal of Nonlinear Analysis and Optimization: Theory & Applications (JNAO), 2013)
In this paper we introduce new classes of generalized Picard operator and obtain some Ulam-Hyers stability results for the operators which extend results in [5]. As application, an existence and uniqueness result for an integral equation is given.